2019
DOI: 10.1001/jamanetworkopen.2019.13325
|View full text |Cite|
|
Sign up to set email alerts
|

Cascades of Care After Incidental Findings in a US National Survey of Physicians

Abstract: This survey study estimates the national frequency and consequences of cascades of care after incidental findings using results from a national survey of US physicians.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
133
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 118 publications
(141 citation statements)
references
References 54 publications
(124 reference statements)
4
133
0
Order By: Relevance
“…1 , 2 Examples include cancer screening for patients with a limited life span or performing preoperative electrocardiography for patients undergoing low-risk cataract surgery. 3 , 4 Up to 43% of Medicare beneficiaries have received low-value care, which may be associated with physical and psychological harm and an erosion of their trust in the health care system. 5 , 6 …”
Section: Introductionmentioning
confidence: 99%
“…1 , 2 Examples include cancer screening for patients with a limited life span or performing preoperative electrocardiography for patients undergoing low-risk cataract surgery. 3 , 4 Up to 43% of Medicare beneficiaries have received low-value care, which may be associated with physical and psychological harm and an erosion of their trust in the health care system. 5 , 6 …”
Section: Introductionmentioning
confidence: 99%
“…4 This is also important because incidental findings on diagnostic tests are common and often trigger unnecessary testing and treatment. 5 Another potential solution could be to implement pre-authorization from on-call radiologists or, in the VA, utilizing available teleradiology services to curb this problem. Finally, more efforts should be focused on disseminating the best practices to providers.…”
mentioning
confidence: 99%
“…1 Nearly 90% of physicians reported that a cascade had caused patient harm, including psychological harms, treatment burden, financial burden, and physical harm. 1 Cascades also negatively affected physicians in terms of wasted time and effort, frustration, and anxiety. 1 Notably, approximately half of physicians experienced a cascade when they or family members were patients.…”
mentioning
confidence: 99%
“…1 Cascades also negatively affected physicians in terms of wasted time and effort, frustration, and anxiety. 1 Notably, approximately half of physicians experienced a cascade when they or family members were patients. 1 Consider first that cascades are core to the practice of medicine.…”
mentioning
confidence: 99%
See 1 more Smart Citation